Hashimoto’s thyroiditis and thyroid hormone sensitivity in euthyroid individuals: their association with carotid plaque in northeast China - Wu, Yanmeizhi; Sun, Jingxue; Ni, Yanan; Wang, Minnan; Qiao, Hong (Frontiers in Endocrinology, 2025)
BackgroundCarotid plaque is a hallmark of systemic atherosclerosis, which underlies the pathology of cardiovascular and cerebrovascular events. Both thyroid hormones and Hashimoto’s thyroiditis (HT) affect carotid plaque formation, but their impact on individuals with normal thyroid function remains unclear.MethodsClinical data, including demographics and medical history, were collected. Carotid and thyroid ultrasound, thyroid function tests, thyroid autoantibody measurements, and lipid profiles were performed. A retrospective analysis was conducted to explore the correlation of Hashimoto’s thyroiditis (HT) and thyroid hormone sensitivity with carotid plaque risk in euthyroid individuals, with additional subgroup analyses.ResultsA total of 459 euthyroid patients were included. Thyroid hormone sensitivity indices were higher in the HT group than in the non-HT group. Significant differences in gender, age, smoking duration, diabetes mellitus (DM), coronary artery disease, ischemic stroke, and thyroid hormone sensitivity were observed between patients with and without carotid plaque. Among these factors, sex, age, coronary heart disease, and thyroid hormone sensitivity were identified as independent risk factors for carotid plaque. Differences in plaque size and thickness were noted between the HT and non-HT groups. Notably, in patients with DM, findings regarding plaque risk and characteristics diverged from those in other subgroups.ConclusionIn euthyroid individuals, HT impairs thyroid hormone sensitivity. Increased thyroid hormone sensitivity (as reflected by higher sensitivity indices) elevates carotid plaque risk. While HT may exert a modest protective effect against plaque formation, it contributes to the deterioration of plaque quality in patients with diabetes mellitus and dyslipidemia and elderly individuals with increased thyroid hormone sensitivity.